Cardiomyocyte-derived exosomes carrying miR-181a-5p facilitate heart-brain crosstalk and exacerbate methamphetamine dependence in rats - Hancheng Li; Hancheng Li; Hancheng Li; Yongen Peng; Yangkai Wu; Yangkai Wu; Yiling Chen; Yiling Chen; Jieyu Li; Jieyu Li; Yunbing He; Yunbing He; et al. (Frontiers in Pharmacology)
BackgroundMethamphetamine (MA) is one of the most harmful synthetic drugs, yet the mechanisms underlying its addiction and relapse remain incompletely understood. This study investigates how cardiomyocyte-derived exosomes carrying miRNAs facilitate heart-brain crosstalk and contribute to MA dependence.Materials and methodsA conditioned place preference (CPP) model of MA dependence was established in rats. High-throughput sequencing were employed to identify candidate miRNAs in cardiac exosomes and brain tissues. Behavioral assessments, real-time PCR, nanoparticle tracking analysis, in vivo imaging, in vitro uptake assays, network pharmacology, and dual-luciferase reporter assays were used to explore the role of cardiomyocyte-derived exosomes in MA dependence.ResultsMA induced significant CPP in rats. miR-181a-5p was markedly upregulated in cardiac exosomes and brain tissue, with higher levels observed in cardiac exosomes. In vivo biodistribution showed that cardiomyocyte-derived exosomes cross the blood-brain barrier and accumulate in the brain. In vitro uptake assays demonstrated that SH-SY5Y cells internalized these exosomes, leading to increased miR-181a-5p expression. Tail vein injections of miR-181a-5p-enriched exosomes enhanced MA CPP behavior in rats. Network pharmacology revealed 108 potential targets of miR-181a-5p, enriched in processes such as steroid biosynthesis, amide metabolism, and apoptosis, involving pathways related to the endoplasmic reticulum, MAPK signaling, and amyotrophic lateral sclerosis. Molecular docking identified stable interactions between MA and 12 targets, including HSP90B1, TNF, and MAP2K1, with miR-181a-5p binding to the 3′-UTR regions of these targets. Dual-luciferase assays confirmed the negative regulation of six targets by miR-181a-5p.ConclusionThis study reveals that cardiomyocyte-derived exosomes transport miR-181a-5p, facilitating heart-brain crosstalk and exacerbating MA CPP behavior in rats. These effects are mediated through the regulation of key brain targets, including HSP90B1, TNF, and MAP2K1, providing new insights into the molecular mechanisms of MA addiction and potential therapeutic targets.